PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN TERHADAP KEPERCAYAAN DIRI IBU MERAWAT BAYI PREMATUR DI RSAB HARAPAN KITA JAKARTA BARAT - Febi Puspitasari (2023)
The increase in the number of premature births in Indonesia as much as 28.11% at this time raises various health problems that will be experienced. These problems are associated with developmentally inappropriate infants and a significant cause of childhood morbidity, with many surviving at increased risk of lifelong disability and poor quality of life, including neonatal morbidity, delays in motor, cognitive and behavioral development in young children. early childhood, learning disabilities, vision and hearing problems, and an increased risk of chronic diseases such as cardiovascular disease and diabetes. In addition, the importance of mother's knowledge and mother's confidence in caring for premature babies at home is a major factor. To increase mother's confidence, it is necessary to provide appropriate health education. This study aims to analyze the effect of providing health education on the self-confidence of mothers caring for premature babies at Harapan Kita Hospital, West Jakarta. The research method used in this study was a quasy experimental non-randomized control trial with Paired T test data analysis. Sampling was carried out using purposive sampling technique with a total of 30 respondents who had given birth to premature babies in the April-June range. Based on the results of the data analysis that has been done, it was found that there was an effect before being given health education and after being given health education on the confidence of mothers caring for premature babies.